2015
DOI: 10.1021/am5076309
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide)-Based Mixed Brushes: A Computer Simulation Study

Abstract: Temperature-sensitive poly(N-isopropylacrylamide) (PNIPAM) polymer brushes of fixed molecular weight and grafting density are modeled in the framework of a coarse-grained model with soft, nonbonded interactions and an implicit solvent. This model has been developed to address experimentally relevant, large invariant degrees of polymerization, and nonbonded interactions are expressed via a third-order (virial) expansion of the equation of state. The choice of interaction parameters is intended to mimic the swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 62 publications
5
35
0
Order By: Relevance
“…For the assembled structure, we obtain a less pronounced change with temperature of the individual properties of the chains, as found in arrangements of polymer brushes for coarse-grained models with an implicit solvent. 30 Nonetheless, results show a small drop of the average gyration radius of the molecules at a temperature T Θ consistent with the one obtained for a single 30-mer, for both force fields. Finally, we immerse the membrane in 1M NaCl and NaI solutions, to get the ionic profiles below and above T Θ .…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…For the assembled structure, we obtain a less pronounced change with temperature of the individual properties of the chains, as found in arrangements of polymer brushes for coarse-grained models with an implicit solvent. 30 Nonetheless, results show a small drop of the average gyration radius of the molecules at a temperature T Θ consistent with the one obtained for a single 30-mer, for both force fields. Finally, we immerse the membrane in 1M NaCl and NaI solutions, to get the ionic profiles below and above T Θ .…”
Section: Introductionsupporting
confidence: 87%
“…This feature is consistent with results of polymer brushes, where increasing brush grafting density and/or decreasing temperature leads to an increase of the end-to-end distance. 30 Thus, in the membrane configuration, we should avoid referring to the more compact structure as globule, although longer chains should produce such structure. This result may suggest that a finite chain concentration forming a dehydrated phase may stabilize the coil structure, but note that this could be true only for this particular arrangement (parallel chains).…”
Section: B Membrane In Pure Watermentioning
confidence: 99%
“…Longhi et al studied PNIPAM oligomers consisting of 50 monomers at 300 K and at 310 K (i.e., below and above the LCST), 16 and observed a coil-to-globule transition and reduced number of water molecules in the first coordinate shell of PNIPAM at 310 K as compared to 300 K suggesting different arrangement of hydrophobic groups at the two temperatures. 16 There are several experimental and computational investigations of PNIPAM based architectures such as hydrogels 4,6,21,22 and brushes, 23 including our previous work on the effect of cross-linker length on the structural and dynamical properties of PNIPAM hydrogels across its LCST. 20 Our results revealed that the cross-linker length did not affect the temperature of the onset of the LCST, although the degree of swelling and pore size distribution in these hydrogels were strongly dependent on the length of cross-linkers.…”
Section: I) Introductionmentioning
confidence: 99%
“…Dimensionless variables that are suitable for interpretation of the system temperature are introduced to carry out the simulations. The temperature of reference T * = 298.15K is used to scale the temperatures, thus the simulation temperature T ranges from 0.95 to 1.15ε/k B to represent different system temperatures T * = 10–70 °C . All the simulation runs were conducted with 2 × 10 6 time steps for system equilibrium, and the last 10 5 time steps were used for morphology analysis.…”
Section: Simulation Approachesmentioning
confidence: 99%
“…The temperature of reference T * = 298.15K is used to scale the temperatures, thus the simulation temperature T ranges from 0.95 to 1.15ε/k B to represent different system temperatures T * = 10-70 °C. [46][47][48] All the simulation runs were conducted with 2 × 10 6 time steps for system equilibrium, and the last 10 5 time steps were used for morphology analysis. The images in this work are generated with the molecular visualization program VMD (Visual Molecular Dynamics).…”
Section: Simulation Approachesmentioning
confidence: 99%